2013
DOI: 10.1007/s11255-013-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary monopolar and bipolar transurethral resection of the prostate: prospective assessment of complications using the Clavien system

Abstract: A modified Clavien system can be considered a practical and easily applicable tool in grading postoperative complications in patients undergoing TURP. Our findings confirm that TURP is a safe procedure associated with minimal perioperative morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…16 In our series TURP was effective in improving LUTS and Q max with a low morbidity rate. The incidence of postoperative complications was 10.6% and few high-grade complications were observed.…”
Section: Resultssupporting
confidence: 47%
See 2 more Smart Citations
“…16 In our series TURP was effective in improving LUTS and Q max with a low morbidity rate. The incidence of postoperative complications was 10.6% and few high-grade complications were observed.…”
Section: Resultssupporting
confidence: 47%
“…These data are in line with those reported in other studies evaluating TURP complications using the CCS. 16 We observed a more significant improvement in terms of LUTS and OAB scores in patients with PCI when compared to those without prostatic inflammatory infiltrates. Inflammation was associated with a 55% reduction risk of higher postoperative storage symptoms (sIPSS !4).…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Persistent nocturia was defined as ≥2 episodes per night. Postoperative complications were recorded and classified according to the modified Clavien classification system …”
Section: Methodsmentioning
confidence: 99%
“…The authors proposed that transient hematuria, acute urinary retention, and UTI be considered grade I; hematuria requiring blood transfusion or UTI with bacteremia grade II; extraperitoneal fl uid collection grade III; and fi nally myocardial infarction, respiratory distress, and TUR syndrome as grade IV. These authors concluded that TURP is a procedure whose complications can mostly be categorized into low Clavien grades [ 37 ].…”
Section: Complicationsmentioning
confidence: 99%